2002
DOI: 10.1021/jo025508u
|View full text |Cite
|
Sign up to set email alerts
|

Photochemical Synthesis of Aldehydes in the Solid Phase

Abstract: A substituted anthraquinone (AQ), previously shown to photochemically generate benzaldehyde in methanol solution, was attached to a commercially available resin via an 11 carbon tether and an amide bond. Photolysis of the polymer-bound AQ with visible or 350 nm UV light resulted in the formation of benzaldehyde in yields of 50-55% as determined by HPLC. The phenolic positions in the polymer were then alkylated using benzyl bromide and 1-iodo-3-(4-nitrophenyl)propane in a coupling reaction with K(2)CO(3) as a b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
16
0
2

Year Published

2006
2006
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 34 publications
0
16
0
2
Order By: Relevance
“…9-11 Substituted and unsubstituted citral precursors 1-5 were prepared from their corresponding hydroxyanthraquinones by etherification with geranyl bromide and potassium carbonate in 2-butanone, according to the procedure of Blankespoor et al 8 Whereas the etherification reaction proceeded well with allylic geranyl bromide, almost no reaction occurred under the same conditions when (2-bromoethyl)benzene was used as the alkylating agent, even after prolonged reaction times. Anthraquinone ethers of 2-phenylethanol (6), hexylcinnamol (7) …”
Section: Preparation Of Precursorsmentioning
confidence: 99%
See 2 more Smart Citations
“…9-11 Substituted and unsubstituted citral precursors 1-5 were prepared from their corresponding hydroxyanthraquinones by etherification with geranyl bromide and potassium carbonate in 2-butanone, according to the procedure of Blankespoor et al 8 Whereas the etherification reaction proceeded well with allylic geranyl bromide, almost no reaction occurred under the same conditions when (2-bromoethyl)benzene was used as the alkylating agent, even after prolonged reaction times. Anthraquinone ethers of 2-phenylethanol (6), hexylcinnamol (7) …”
Section: Preparation Of Precursorsmentioning
confidence: 99%
“…Based on recent publications from Brinson and Jones 7 and Blankespoor et al 8 who reported the photochemical release of aldehydes from 1-alkoxy-9,10-anthraquinones, we considered the potential use of this substrate for the light-induced controlled release of fragrance aldehydes or ketones. The precursors are ethers and should thus be stable in most of the application bases currently used.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Für die Immobilisierung an ein Polymer stehen unzählige Methoden zur Verfügung, [3] wobei sehr wichtig ist, dass die Reaktivität und Selektivität des niedermolekularen Reagenzes oder Katalysators erhalten bleiben. In der organischen Photochemie spielen immobilisierte Katalysatoren bislang keine große Rolle, [4][5][6] was nicht überrascht, da das Reagens der Photochemie per Definition das Licht ist. In Zusammenhang mit unseren Arbeiten zu enantioselektiven photochemischen Umwandlungen in Lösung, aus denen das hoch selektive chirale Komplexierungsreagens 1 [7][8][9] hervorging (Schema 1), haben wir nun auch die Immobilisierung dieses Templats an ein Polymer untersucht.…”
unclassified
“…Der Einfluss der Konfiguration an C6 auf die Stereoselektivität der geplanten Photoreaktion ist gering. In der Tat beruht die Enantioselektivität ja darauf, dass 1) ein Substrat einer photochemischen Reaktion an das NHCO-Bindungsmotiv des 2-Oxo-3-azabicyclo[3.3.1]nonan-Rings andockt und dass 2) eine vollständige Differenzierung der enantiotopen Seiten des Reaktanten durch das 5,6,7, …”
unclassified